Academics Alone Together: Liberal Arts Graduate Students' Writing Networks - Mary Hedengren; Hannah V Harrison (University of Windsor, 2018)
Graduate writers who develop networks of writing are positioned to enter into the larger discourse community during and after graduate work. Our study surveyed graduate writers in the humanities about the sources of writing feedback they use and how much they trust or fear those sources. The results indicate that graduate students do employ a variety of sources and strategically assess when and how to use those sources. Still, many graduate students do not get frequent feedback on their writing, and others believe "we take what we get" in writing feedback. Student services who serve graduate students should work in conjunction with graduate program administrators and advisors to encourage students to develop effective networks of writing feedback, including important peer networks.